THE INHERITANCE AND INNOVATION OF TRADITIONAL CULTURE IN THE NEW MEDIA ENVIRONMENT - Jiang Xudong; Hamisah Hasan (Journal of Islamic, Social, Economics and Development, 2024)
With the rise and proliferation of new media, traditional culture is encountering novel opportunities and challenges in the digital era. This paper aims to delve into the inheritance and innovation of traditional culture within the new media landscape. Employing a methodological approach that incorporates both qualitative and quantitative analyses, we begin by dissecting the definition and characteristics of traditional culture, followed by an examination of the influence of new media on the transmission of traditional culture. This allows for a thorough understanding of the development status of traditional culture in the digital age and facilitates a discussion on modes of inheritance and innovation paths within the context of new media. Moreover, this paper investigates the challenges faced by traditional culture in the new media environment, such as information fragmentation, the depth of cultural inheritance, and the conflicts between traditional cultural values and new media values. Methodologically, this research adopts a mixed-methods approach, blending content analysis of digital media, surveys of cultural consumers, and interviews with practitioners to capture a multifaceted perspective. In conclusion, the paper underscores the significance of inheriting and innovating traditional culture in new media settings and offers a forward-looking perspective on future developments, suggesting strategies to further promote the inheritance and innovation of traditional culture in the age of new media. The research presented in this paper contributes to a better comprehension of the relationship between traditional culture and new media, aids in the promotion of the inheritance and innovation of traditional culture, and drives the expansion of cultural diversity and creativity.